2020
DOI: 10.1080/15538362.2020.1768618
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure Analysis of Coffee (Coffea canephora) Germplasm Collections in Indian Gene Bank Employing SRAP and SCoT Markers

Abstract: Coffea canephora Pierre ex Frohener is popularly known as robusta coffee contributes to about 39% of the total world coffee production. Coffea canephora a native to West Africa was introduced to India as early as 1900 AD. However adequate information regarding the diversity and genetic structure of C. canephora germplasm available in India is not yet available. In the present study, sequence related amplified polymorphism (SRAP) and start codon targeted (SCoT) molecular markers were employed to access the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Characterizations by molecular markers performed by Souza et al (2013), Solórzano et al (2017) and Huded et al (2020 also revealed wide genetic diversity in C. canephora and reinforce the importance of this information for the hybridization between germplasms and for the composition of clonal varieties…”
Section: Discussionmentioning
confidence: 78%
“…Characterizations by molecular markers performed by Souza et al (2013), Solórzano et al (2017) and Huded et al (2020 also revealed wide genetic diversity in C. canephora and reinforce the importance of this information for the hybridization between germplasms and for the composition of clonal varieties…”
Section: Discussionmentioning
confidence: 78%
“…The excellent coffee genome-wide sequence has made it feasible to identify the gene and protein components in coffee cherries by using transcriptomic and proteomic analytical approaches [ 11 ]. Transcriptomics by itself was unable to precisely forecast the amount of proteins and the activity of proteases [ 12 ]. Low-molecular-weight metabolites and high-molecular-weight proteins as well as the dynamic state of the cell could be analyzed qualitatively and quantitatively using combined metabolomics and proteomics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, omics technology has been considered an effective way to reveal the relationship between metabolites, proteins, and genes [ 9 ]. The high-quality coffee genome-wide sequence has made it possible to apply transcriptomic and proteomic analysis techniques to detect the gene and protein compositions in coffee cherries [ 10 , 11 ], while applying transcriptomics alone could not accurately predict the protein abundance and protease activity [ 11 ]. Combined metabolomics and proteomics could be used for qualitative and quantitative analyses of low-molecular-weight metabolites and high-molecular-weight proteins, and the dynamic state of the cell, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%